SOCIALISTIC TRANSFORMATIONS IN DAGESTAN IN THE FIRST DECADE OF THE SOVIET RULE - Muslimova, Naida Tagirova (History, Archeology and Ethnography of the Caucasus, 2019)
Based on a wide range of documented sources and research works of both Russian and foreign scholars, the article overviews the mechanism of those large-scale and contradictory changes, which took place in the Dagestan society as a result of the new economic policy, implemented by the Soviet government in 1921-1928. The interest to the history of the socialistic transformations in Dagestan is again relevant, given the fact that, on the one hand, modern historiography pays great attention to alternative ways of developing the country and the republic, and on the other, post-Soviet changes in social development have led to catastrophic results. This underlines the need for reconsideration of the soviet experience. The method of comparative analysis is used in the study. It shows that in the specific historical conditions of Dagestan, the diversified economy, the introduction of market management methods, cost-accounting elements and at the same time systematic financial and material and technical assistance of the Soviet government became a catalyst for the destruction of the traditional structure of Dagestan society; its differentiation, and changes in it social-class composition, which to a certain extent prepared the Dagestanis for the adoption of the Stalinist model the development of Soviet society. The processes of transformation of Dagestan society are considered in the article through the prism of the ideological struggle that took place in the higher levels of the ruling party in the first decade of Soviet power.